Regulatory changes in pterin and carotenoid genes underlie balanced color polymorphisms in the wall lizard - Andrade, Pedro; Pinho, Catarina; Pérez I de Lanuza, Guillem; Afonso, Sandra; Brejcha, Jindřich; Rubin, Carl-Johan; Wallerman, Ola; Pereira, Paulo; Sabatino, Stephen J; Bellati, Adriana; Pellitteri-Rosa, Daniele; Bosakova, Zuzana; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Reptiles use pterin and carotenoid pigments to produce yellow, orange, and red colors. These conspicuous colors serve a diversity of signaling functions, but their molecular basis remains unresolved. Here, we show that the genomes of sympatric color morphs of the European common wall lizard (Podarcis muralis), which differ in orange and yellow pigmentation and in their ecology and behavior, are virtually undifferentiated. Genetic differences are restricted to two small regulatory regions near genes associated with pterin [sepiapterin reductase (SPR)] and carotenoid [beta-carotene oxygenase 2 (BCO2)] metabolism, demonstrating that a core gene in the housekeeping pathway of pterin biosynthesis has been coopted for bright coloration in reptiles and indicating that these loci exert pleiotropic effects on other aspects of physiology. Pigmentation differences are explained by extremely divergent alleles, and haplotype analysis revealed abundant transspecific allele sharing with other lacertids exhibiting color polymorphisms. The evolution of these conspicuous color ornaments is the result of ancient genetic variation and cross-species hybridization.
Keywords: Carotenoids; pigmentace kůže; Pigmentation; polymorfismus genetický; ještěři; Skin Pigmentation; alkoholoxidoreduktasy; Color; zvířata; karotenoidy; pigmentace; Polymorphism, Genetic; barva; dioxygenasy; Dioxygenases; pteriny; Lizards; Animals; Alcohol Oxidoreductases; Pterins